An Unusual Case of Genital Lesion: A Vulvar Syringoma - Paola Algeri; Rosita Rodella; Cinzia Manfredini; Maurizio Algeri (Tehran University of Medical Sciences, 2021)
Objective: Syringoma is a benign adnexal neoplasm of sweat gland, usually presenting as extra-genital lesions, while vulvar localization is rare. Moreover, syringoma is an uncommon vulvar neoplasms. Case report: A 44-year-old woman with previous diagnosis of duodenal gastrointestinal stromal tumour, underwent a local surgical excision for an isolated, painful, vulvar lesion. The specimen was submitted for histological examination. A vulvar syringoma was diagnosed. Conclusion: We describe this case according on its rarity and atypical presentation as well; therefore, vulvar neoplasms encompass many differential diagnoses, among which the incidence rate of syringoma is very low. Although its rarity, syringoma should be included among the differential diagnosis for vulvar neoplasm.